Equatorial Guinea : Public Expenditure Review - World Bank (World Bank, 2012)
This Public Expenditure Review (PER) is the result of collaboration between the World Bank and the Government of Equatorial Guinea. The main goal of the agreement and this report is to assist the Government of Equatorial Guinea to better implement its National Development Plan (NDP) and meet the challenges of diversifying the economy beyond petroleum production and reducing poverty. The data in this report is based on the available information at the time of preparation (2008 and 2009). Rapidly rising oil income since 1991 has made Equatorial Guinea comparatively wealthy, although poverty reduction has lagged behind. The government is eager to accelerate implementation of the NDP by improving economic governance in the public sector. Indeed, sustainable economic growth, job creation and poverty reduction can only be achieved through productivity increases in the non-oil economy. Incomplete and poor quality economic data has also hindered preparation of this report. Finally, the insufficiency of social sector public expenditures is inconsistent with the NDP's stated goals for economic diversification and poverty reduction.